An empirical Analysis of Behavior Management Counsel for students - Suson, Roberto; Malabago, Nolasco; Capuyan, Dennis; Galamiton, Narcisan; Ermac, Eugenio (International Journal of Psychosocial Rehabilitation, 2020)
This study was designed to assess the influence of teachers behavioral management in relation to the common behavioral problem of the students. These variables were investigated to measure the effectiveness of behavior management to the students’ behavior in the school. The descriptive method of research was used in this research. A Survey questionnaire was formulated to gather the needed data from the respondents. Further, percentages, weighted mean, frequency were used to analyze the and interpret the data, and chi-square for the significant difference. The findings revealed that behavior management strategies have huge influence in dealing with students common behavioral problem. Undesirable behaviors were addressed as well across the study. Moreover, reinforcements were the topmost utilize behavior management of the teachers and punishment was the least used. This entails that teachers develop students through their potential by giving and intangible rewards such as praises and good grades. Those particular behavior management help the teachers in dealing with disruptive/undesirable among students.